The influence of sex and age on ventricular arrhythmia in a population-based registry. (1st October 2017) - Styles, Kimberly; Sapp, John; Gardner, Martin; Gray, Christopher; Abdelwahab, Amir; MacIntyre, Ciorsti; Gao, Dongsheng; Al-Harbi, Mousa; Doucette, Steve; Theriault, Chris; Parkash, Ratika
Abstract: Background: Post-hoc analyses of clinical trials and population-based studies have shown no difference in mortality between men and women, but often show that men are more likely to receive appropriate ICD therapy. We utilized a population-based registry to investigate the interaction of sex and age and the occurrence of ventricular arrhythmia in an ICD population. Methods and results: A total of 776 consecutive patients receiving an ICD for primary or secondary prevention in a provincial ICD registry were studied. No significant mortality difference was found between men and women (27.5% versus 23.7%, p = 0.39). Overall, men were more likely to receive appropriate ICD therapy compared to women (39.3% versus 26.7%, p = 0.006). The hazard ratio for appropriate therapy in men vs. women < 60 years of age was 3.22, CI 95% (1.56–6.65), p = 0.002, and the same comparison in men vs. women over the age of 60 showed no significant difference (HR 1.11, CI 95% [0.74–1.65], p = 0.61). This interaction between age and sex remained significant when adjusted for New York Heart Associated Class, ejection fraction, coronary artery disease and indication for ICD (p = 0.02). Conclusions: This study demonstrates that the risk of appropriate ICD therapy increases as women are older, reaching similar risk as men in that age group. Further study of the mechanism of the interaction of age and sex as they modulate the occurrence of ventricular arrhythmia may be warranted.